The impact of the COVID-19 restrictions on women"s responsibility for domestic food provision: The Case of Marondera Urban in Zimbabwe - Matanga, Sarah Y. (HTS teologiese studies, 2023)
When pandemics hit communities, women are bound to suffer as most of the responsibilities of ensuring food security lie on them. This article assesses the impact of the COVID-19 pandemic on the role that church-going women play in food provision. The qualitative study used interviews and focus group discussions to examine the toll of the pandemic-induced restrictions, especially with regard to their disruption of activities that ensure the provision of food for the family. They sought to identify how an environment as restrictive as the one that was imposed during the COVID-19 pandemic affects those largely responsible for food provision in urban Marondera – the women, in this case. The focus was extended to factor in how disasters and pandemics affect women and detract from their normative food procurement and provision roles in marginal societies and how these effects can be mitigated to allow women to carry on with their roles even in restrictive environments. This research was motivated by the recent COVID-19-imposed regulations that restricted the movement of people, restrictions that have only recently been relaxed and (in some cases) removed. We also sought to establish how gender roles are played out, together with whether they are exacerbated by pandemics, and in what ways these pandemics result in higher workloads on women. By utilising the Africana womanist theory, the study analysed women roles in food provision and food security in their societies within the restrictive environments of the pandemics.Contribution: This study concluded that there are gender inequalities that are exacerbated by these pandemics that result in higher workloads for women. It foregrounded how existing gender inequalities were exacerbated by the pandemic, resulting in higher workloads on women. It therefore recommended that women should form empowerment groups to help focus attention on food provision to mitigate challenges women face in this role. Finally, we averred that there ought to be consultation and participation of women on issues to do with pandemics to allow for their full and productive participation in critical roles of providing food.